Extract Tamarillo (Solanum Betaceum) as Natural Dye for Formulation of Moisturizing Lip - Laurani, Destyc Pratiwi; Kusumayanti, Heny; Afiyanto, Putri Solihah; Revabelita, Aisha (Journal of Vocational Studies on Applied Research, 2024)
The cosmetics industry is experiencing rapid growth, offering a diverse array of products designed to enhance appearance and promote skin health. Among these products, lip moisturizers are particularly important, serving to maintain lip moisture and health while enhancing attractiveness. The trend toward natural ingredients in cosmetics is on the rise due to their perceived safety and environmental benefits compared to synthetic alternatives. In this study, tamarillo (Solanum betaceum) extract is utilized as both a nutrient and a natural colorant in lip balm. Tamarillo is rich in anthocyanins, which provide natural coloration and antioxidant properties, helping to combat free radicals, hydrate, soften the skin, and reduce dryness. This research aims to develop a lip balm formulation incorporating tamarillo extract at varying concentrations. The study is conducted experimentally, with lip balm formulations prepared using tamarillo extract at 4% and 6% concentrations. The lip balm's quality is assessed through organoleptic testing, homogeneity, stability, melting point, pH, irritation potential, and moisturizing effectiveness over a two-week period. The resulting lip balm product is anticipated to be an innovative solution for addressing dry, chapped, and dull lips, with potential for further development.